INVESTIGATION ON THE EFFECT OF SHAPES ON THE DRYING KINETICS AND SENSORY EVALUATION STUDY OF DRIED JACKFRUIT - Pek Li Gan; Phaik Eong Poh (International Journal of Science and Engineering, 2014)
Jackfruits are seasonal and highly nutritional fruits indigenous to the Southwestern rainforests of India. However much of the produce are spoilt annually due to poor preservation techniques. Minimal studies have been conducted on the drying kinetics of jackfruit and the effect of shapes on the drying kinetics. In this research, drying curves of three different shaped jackfruit slices were obtained using a convective oven at 40oC, 50oC, 60oC and 70oC. Modified Midilli-Kucuk Model was found to be the best kinetic model for drying of jackfruits. At all temperatures, effective moisture diffusivity values and activation energy varied from 2.66 x 10-10 - 4.85 x 10-10 m2/s and 16.08 - 20.07 kJ/mol respectively. Drying was found to be most efficient at 50oC using the square shaped slices with a R2, RMSE and SSE value of 0.9984, 0.01127 and 0.002668 respectively.  Sensory evaluation of untreated and additive-added dried jackfruit slices was conducted by 40 untrained sensory panelists. Jackfruit with ascorbic acid and sugar coating had highest aesthetics value due to better retention of colour by ascorbic acid. However sugar coated jackfruit had the most favorable taste and smell. Further optimization must be done to satisfy consumers collectively to enable a highly marketable product.